2005
DOI: 10.1007/s11010-005-2993-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serum lipids and high-density lipoprotein subfractions (HDL2, HDL3) in postmenopausal patients with breast cancer

Abstract: Breast cancer patients are known to be at increased risk for developing other chronic diseases including cardiovascular disease. Studies by different investigators have shown a correlation between increased dietary fat or hypercholesterolemia and the occurrence of breast cancer. Since previous studies on lipoprotein subfractions in this type of cancer have been inconsistent, we evaluated the lipids and lipoprotein subfraction levels in postmenopausal patients with breast cancer in an attempt to identify the ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
60
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 27 publications
7
60
0
Order By: Relevance
“…The association between HDL-C and breast cancer risk by menopausal status has been inconsistent among studies (13,(26)(27)(28)(29)(30)(31)(32)(33). However, several results show consistent results of our study.…”
Section: Resultssupporting
confidence: 82%
“…The association between HDL-C and breast cancer risk by menopausal status has been inconsistent among studies (13,(26)(27)(28)(29)(30)(31)(32)(33). However, several results show consistent results of our study.…”
Section: Resultssupporting
confidence: 82%
“…This association persisted after adjustment for age, body size, lipids, reproductive and familial risk factors, and previous benign breast problems (p<0.01), in keeping with an independent association of elevated TG with breast cancer risk [28]. Several studies have also shown significant increase in TG levels of breast cancer patients [21][22][23][24]27]. However, other studies did not demonstrate a statistically significant increase in TG levels.…”
Section: Discussionmentioning
confidence: 64%
“…Borrelli et al suggesedt that a high serum HDL-C could be a biochemical index of increased risk of having breast cancer [20]. Studies by Qadir et al [9], Shah et al [21], Michalaki et al [22], Kökoğlu et al [23] and Bani et al [24] have also shown an increase in HDL-C to be associated with an increased risk of breast cancer. In contrast to these findings, other studies suggest that low HDL cholesterol may be a marker of increased breast cancer risk among premenopausal [25] and postmenopausal women [26].…”
Section: Discussionmentioning
confidence: 99%
“…Some experts suggest that suppressed HDL and elevated triglycerides in patients are risk factors for colon (Giovannucci, 2001), breast (Furberg et al, 2004;Michalaki et al, 2005), and prostate cancers (Hammarsten and Hogstedt, 2004). Besides that Wuermli L found hypertriglyceridemia may be a prognostic indicator for prostate cancer according to one recent Swiss case control study that controlled for age, BMI, diabetes mellitus, and statin medication.…”
Section: Discussionmentioning
confidence: 99%